2017
DOI: 10.1186/s12874-017-0448-8
|View full text |Cite
|
Sign up to set email alerts
|

Methods to perform systematic reviews of patient preferences: a literature survey

Abstract: BackgroundSystematic reviews are a commonly used research design in the medical field to synthesize study findings. At present—although several systematic reviews of patient preference studies are published—there is no clear guidance available for researchers to conduct this type of systematic review. The aim of our study was to learn the most current practice of conducting these systematic reviews by conducting a survey of the literature regarding reviews of quantitative patient preference studies.MethodsOur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Owing to a lack of definite guidance on how to perform an appropriate quality assessment for preference-based studies, 28 the methodological quality of the included studies was evaluated by adapting four criteria from two previously published instruments for patient preference studies. 29,30 Two reviewers (AE, AR) independently assessed whether (1) there was a well-defined question in relation to preferences, (2) the characteristics of the participants were clearly described, (3) the respective methods to assess preferences were clearly explained, and (4) the authors reported quality criteria in relation to the elicitation methods used.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Owing to a lack of definite guidance on how to perform an appropriate quality assessment for preference-based studies, 28 the methodological quality of the included studies was evaluated by adapting four criteria from two previously published instruments for patient preference studies. 29,30 Two reviewers (AE, AR) independently assessed whether (1) there was a well-defined question in relation to preferences, (2) the characteristics of the participants were clearly described, (3) the respective methods to assess preferences were clearly explained, and (4) the authors reported quality criteria in relation to the elicitation methods used.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…In the last decade, systematic reviews of qualitative and mixed-method research synthesis have provided a more detailed understanding of the complexity of chronic diseases and their treatment from the perspective of patients and their caregivers [ 12 , 13 ]. More recently, there is a growing interest in assessing patients’ preferences and developing systematic reviews of quantitative preferences studies [ 14 ]. However, to date, no systematic analysis has been undertaken of quantitative and qualitative evidence focused on patients’ and caregivers’ preferences for and experiences with SM.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the methodological limitations of the quantification of patients' preferences, the dependence of the sample size and the setting where preferences were elicited, this review revealed that preferences were not stable over time, e.g., before and after a disease-specific intervention or adverse life event [37]. Yu et al highlighted the tremendous heterogeneity in the revealed preferences across different studies, demonstrating that preferences depend on the eliciting methods used [38]. Therefore, further research is needed to assess patient preferences in dementia diseases capturing several domains of diagnostics, treatment, care, and support as well as patient-and caregiver-related outcomes.…”
Section: Discussionmentioning
confidence: 99%